Future designs of tertiary dance education: Scanning the field for decolonizing potentials in a major change project at the Department for Dance Pedagogy at Stockholm University of the Arts - Tone Pernille Østern (Cappelen Damm Akademisk NOASP, 2021)
This performative hybrid research and development project contributes knowledge about the decolonizing potentials and challenges that are articulated through an initial scanning of the dance pedagogical field as part of a large change project in tertiary dance education at the Department for Dance Pedagogy at Stockholm University of the Arts in Sweden. To do this scanning in a way that would promote collective learning, multiple perspective taking and creativity, we utilised design thinking. In total, 140 scan cards collected through the project were analysed. Both students and staff and other people in different parts of the world within the dance educational field created the scan cards. As a result, we suggest that the scanning of the field has pushed ourselves, the rest of the staff, students, and others into a process of collective learning, multiple perspective taking, and creativity, in which clear decolonizing potentials, as well as challenges to change are expressed.